The essentials of conditioning and learning - Domjan, Michael, 1947- (American Psychological Association, 2018)
"Now in its fourth edition, Michael Domjan's classic textbook offers an introduction to learning and conditioning in a concise and accessible style, including the latest influential research findings and theoretical perspectives. Basic principles of learning and conditioning are relevant to an increasingly broad range of psychologists and neuroscientists. Yet in recent years, these core areas have become less prevalent in psychology and neuroscience curricula. As a result, many researchers today lack the training to understand key concepts that underlie human development and behavior. Moreover, while the field of learning and conditioning is more than a hundred years old, new discoveries continue to be made and new applications of basic research are tackling major clinical problems. Domjan summarizes these developments as well as basic learning and conditioning principles using both human and animal examples. Students and scientists from multiple areas of psychology and neuroscience will value this succinct overview of the processes and mechanisms responsible for conditioning and learning."--Preface. (PsycINFO Database Record (c) 2017 APA, all rights reserved)